Consumer ethnocentrism: What we learned and what we need to know? – A systematic literature review - Ruturaj Baber; Shilpa Sankpal; Prerana Baber; Chanda Gulati (Cogent Business & Management, 2024)
This systematic literature review aims to synthesize the academic research on consumer ethnocentrism comprehensively. The study systematically examines the development of consumer ethnocentrism research over time, including publication years, publication outlets, authorship, countries, methods, and theories utilized. Based on the synthesized literature, this review proposes a conceptual framework that integrates consumer ethnocentrism's reported antecedents, mediators, and consequences. Furthermore, a lexicometric analysis is conducted to identify key themes and trends in consumer ethnocentrism research. The review also identifies under-researched areas in consumer ethnocentrism and provides directions for advancing future research, emphasizing theory development, contextual considerations, characteristics, and methodologies. Overall, this systematic review significantly contributes to the existing body of consumer ethnocentrism literature and offers valuable practical insights for destination marketers and policymakers aiming to implement consumer ethnocentrism strategies effectively.
Keywords: 650; Consumer ethnocentrism; Bibliometric analysis; Conceptual framework; Systematic literature review; TCCM framework